A subversão do cinema clássico pelo surrealismo: a representação do inconsciente psicanalítico no cinema de inspiração surreal - Cardoso, Alexandre Souza (2022)
This research is focused on surrealism in cinema and its particular form of subversion of the classic cinematographic language, which is characterized as a linear narrative structure often submitted to the criteria of industrial production and that seeks to involve the spectator through an impression of reality in the fictional story. The proposal is based on the historical and conceptual delimitation of what the surrealist movement was, dating from the beginning of the 20th century, and the first insertions in the cinema realm, which already presented contrasts to the classic industrial model; next, it will reflect on an expanded surrealism beyond its historical determinations, highlighting its unfoldings in contemporary cinema. Supported by psychoanalytic theory and by authors specialized on cinema, it will consider the influences of the surrealist movement on the psychoanalytic movement and vice-versa, with emphasis on Jacques Lacan's contributions by revisiting Freud's work and his concepts of desire, scopic drive, jouissance, and mirror stage, to think about the surrealist technique, which claims the unconscious in artistic production and the role of language in the formation of images as a procedure that goes back to an "inner model" of the subject, as psychoanalysis has taught us. The corpus of the research includes cinematographic works representative of the school's aesthetic ruptures, focusing on the filmography of directors who present in their signature marks such traces of surrealism, as the contemporary David Lynch, and, in a diachronic cut selection, Jonas Mekas and Maya Deren, exponents of the said to be experimental cinema. The established criteria and the filmic analysis to be developed should explore both the question of the subversion of the classical model by the surreal seen on screen and the subversive experience of the spectator before a cinematographic work that defy the conventions of the real and of reason, as surrealism indicates and which can be associated to the experience of psychoanalytic treatment